1999
DOI: 10.1117/12.368185
|View full text |Cite
|
Sign up to set email alerts
|

Microbeam radiation therapy

Abstract: The central nervous system of vertebrates, even when immature, displays extraordinary resistance to damage by microscopically narrow, multiple, parallel, planar beams of x rays. Imminently lethal gliosarcomas in the brains of mature rats can be inhibited and ablated by such microbeams with little of no harm to mature brain tissues and neurological function. Potentially palliative, conventional wide-beam radiotherapy of malignant brain tumors in human infants under three years of age is so fraught with the dang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
63
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 0 publications
0
63
0
Order By: Relevance
“…1, 2, 7, and 11), (ii) suckling rat cerebellum (150 Gy; ref. 3), (iii) piglet cerebellum (600 Gy; ref. 4), (iv) duckling embryo brain (160 Gy; ref.…”
mentioning
confidence: 99%
“…1, 2, 7, and 11), (ii) suckling rat cerebellum (150 Gy; ref. 3), (iii) piglet cerebellum (600 Gy; ref. 4), (iv) duckling embryo brain (160 Gy; ref.…”
mentioning
confidence: 99%
“…At the ESRF the center-to-center distances between beams range from 100 to 400 µm in MRT and it is 1200 µm in MBRT. The preclinical studies in MRT indicate a remarkable healthy tissue sparing capability [10,11,12,13,14,15] and the ablation of highly aggressive tumours in several animal models [16,17,18,19,20,21,22]. In MBRT, the first preclinical studies indicate that minibeams still keep (part) of the healthy tissue sparing capability observed in MRT [9,23].…”
Section: Introductionmentioning
confidence: 96%
“…1 Experimentally discovered at the Brookhaven National Laboratory 2 and soon afterwards studied at the European Synchrotron Radiation Facilities 3,4 it was shown to have the extraordinary ability of ablating brain tumors while sparing normal tissue in a variety of animals. 5 The absorbed dose threshold for tissue damage using micrometer-width beams was on the order of 10 3 Gy, orders of magnitude higher than that for broad beam radiation.…”
Section: A Microbeam Radiation Therapy (Mrt)mentioning
confidence: 99%
“…5 The absorbed dose threshold for tissue damage using micrometer-width beams was on the order of 10 3 Gy, orders of magnitude higher than that for broad beam radiation. [4][5][6][7] Synchrotron microbeams are generally 25-75 μm in width and spaced 100-200 μm center to center. 6 Studies have shown normal tissue sparing effect is preserved at up to ∼700 μm beam width 8 as long as the valley doses are kept under the threshold values.…”
Section: A Microbeam Radiation Therapy (Mrt)mentioning
confidence: 99%